Oxford Textbook of Children's Sport and Exercise Medicine (Oxford University Press, 2023)
This book presents an integrated, research-driven, collection of 54 evidence-based chapters. Chapters are founded on the research and practical experience of 104 internationally renowned scientists and clinicians, from 25 countries. Each extensively referenced chapter concludes with a bulleted summary and where appropriate is cross-referenced to complementary chapters. The Exercise Science section initially focuses on growth and maturation and the development of motor control, coordination, and muscle strength. Subsequently, molecular exercise physiology, physiological variability, and the perception of exercise are explored and the cerebrovascular, metabolic, endocrine, cardiopulmonary, and neuromuscular responses to exercise are analysed. The Exercise Medicine section opens with a discussion of the role of molecular mechanisms in transducing physical activity and exercise into health benefits. The following chapters analyse physical activity, exercise, and sedentary behaviour and their relationship with cardiovascular health, metabolic syndrome, eating disorders, bone health, diabetes, asthma, cystic fibrosis, cerebral palsy, mental health, and intellectual disability. The Sport Science section reviews bio-banding in youth sport before examining the morphology of youth athletes and analysing the development and trainability of aerobic fitness, anaerobic fitness, speed, and agility. The evidence underpinning resistance, high-intensity, and neuromuscular training is evaluated and overtraining, sleep, temperature regulation, and appropriate assessment, monitoring, and long-term development of youth athletes are discussed. The Sport Medicine section reviews the epidemiology and prevention of injuries before focusing on injuries in physical education classes, and youth sports, and evaluating the role of stretching in injury prevention. The diagnosis and management of injuries to the upper extremity and trunk, the lower limbs, and the head and cervical spine are reviewed. The book concludes with discussions of disability and youth sport, nutrition and eating disorders, dietary supplementation, doping and anti-doping, and safeguarding youth athletes.